OPTIMALISASI PERSALINAN NORMAL MELALUI “BIRTH PREPARATION CENTRE” DI KLINIK BERSALIN KOTA MEDAN TAHUN 2018 - Febrina Oktavinola Kaban; Farida Linda Sari Siregar; Evi Indriani br Karo (Jurnal Riset Hesti Medan, 2019)
Various programs attempt to reduce the maternal mortality rate implemented by the government to pregnant women. The activity "Optimization of Normal Delivery Through Birth Preparation Center" in the Medan City Maternity Clinic" was carried out in two partners. This service partner were Klinik Bidan Eka in Medan Denai and  Klinik Pratama Serasi Medan Helvetia. As many as 80% of pregnant women are afraid of giving birth normally, for reasons of fear of pain that will be experienced later in labor. 85% of pregnant women are negatively pregnant. As many as 90% of pregnant women do not prepare physically. As many as 55% of pregnant women experience hip pain, back pain, and cramps in the legs during pregnancy. 90% of husbands do not motivate their wives. 90% of pregnant women and husbands are anxious about facing childbirth. The methods used are education, hypnobirthing and prenatal yoga. The activities at the Pratama Serasi Clinic were held twice, on 10 and 11 April 2018, this activity was attended by 20 pregnant women. The activities in the second partner were in the Bidan Eka, on May 5, 2018, and was attended by 17 pregnant women. Activities went well and smoothly, publication of activities in Post media massa Sumatera Utara, and Youtube.Keywords: birth preparation, hipnobirthing, yoga prenatal